The Concept of Economic Balance in the Quran: An Interpretation of the Verse Prohibiting Exploitation - Wildan Ashari Hasibuan; Abdillah Nurul Bahri (Taqrib : Journal of Islamic Studies and Education, 2024)
This study aims to explore the concept of economic equilibrium in the Qur'an, focusing on the interpretation of verses prohibiting exploitation, such as exploitation, oppression in trade, and the obligation to act justly. The research employs a qualitative descriptive-analytical approach through a literature study, with primary data consisting of relevant Qur'anic verses (QS. Al-Baqarah: 275-279, QS. Al- Mutaffifin : 1-3, QS. An-Nisa : 135) analyzed using authoritative interpretations. The findings indicate that the Qur'anic prohibition of exploitation not only provides moral guidance but also practical solutions to address modern economic inequalities, such as prohibitions on exploitative exploitation, market manipulation, and hoarding. The concept of economic equilibrium in the Qur'an emphasizes justice, equitable wealth distribution, and social responsibility. This study concludes that Islamic economic values based on Qur'anic teachings offer effective solutions to global economic challenges by creating a fairer, sustainable, and Sharia-compliant economic system.